EXPECTATION OF PERSONS WITH DISABILITIES ON SOCIAL WELFARE OF LOCAL ADMINISTRATIVE ORGANIZATIONS, A CASE STUDY OF RAHAENG SUB-DISTRICT MUNICIPALITY, LAT LUM - SRISUWAN, SAOWANEE (Journal of Social Synergy, 2022)
This study aims to study expectation of social welfare for persons with disabilities, personal factors related to expectation of social welfare for persons with disabilities and recommendations on expectation of social welfare for persons with disabilities in Rahaeng Sub-district Municipality, Lat Lum Kaeo District, Pathum Thani Province. In this survey research, the samples, a total of 152, covered all types of persons with disabilities registering the disabilities and residing in Rahaeng Sub-district Municipality, Lat Lum Kaeo District, Pathum Thani Province. The tool was questionnaire and the statistics for data analysis included frequency, percentage, mean, standard deviation, minimum, maximum, Chi-Square and Correlation. The study results were summarized as follows. 1) Most of the samples were male, aged 60 years and over, had a lower secondary education, were unemployed, resided in Village No. 13, Khlong Rahaeng Pattana Communities, lived in communities for 0-19 years, and had physical or mobility disabilities. 2) Regarding a study on expectation of social welfare for persons with disabilities in Rahaeng Sub-district Municipality, Lat Lum Kaeo District, Pathum Thani Province, it was found that most samples had high overall expectation (mean = 3.83). Regarding a study on personal factors related to expectation of social welfare for persons with disabilities in Rahaeng Sub-district Municipality, Lat Lum Kaeo District, Pathum Thani Province, it was found that the educational level had relationships with expectation of educational welfare of local administrative organizations. 3) Regarding a study on recommendations on expectation of social welfare for persons with disabilities in Rahaeng Sub-district Municipality, Lat Lum Kaeo District, Pathum Thani Province, it was found that most samples (87.50%) had no idea and the others (12.50%) had idea. Classified by social welfare, the ideas are as follows: 1. Health-exercise activities for persons with disabilities, 2. employment and Income maintenance-occupations for persons with disabilities such as tailors, vehicle mechanics, pastry chefs, waste traders, etc., and legal conditions or job markets supporting occupation for persons with disabilities, 3. social service-information, public relations of persons with disabilities and assistance, provided that authorities are coordinators between the public and organizations. Keywords: Expectation, Persons with Disabilities, Social Welfare, Local Administrative Organizations